Method of Memorizing Al Qur'an In Pondok Pesantren Miftahul Jannah East Lampung - Rahayu Hidayah; Mispani Mispani; subandi subandi (Journal of Research in Islamic Education, 2020)
This study aims to describe 1) how the implementation of the Talaqi, Muroja'ah, Sima'I, and Kitabah methods in memorizing Al-Qur'an in the boarding school Tahaffudhul Qur'an. 2) what are the supporters of the implementation of the Talaqi, Muroja'ah, Sima'I, and Kitabah methods in memorizing Al-Qur'an in the boarding school Tahaffudhul Qur'an. 3) What are the obstacles to the implementation of the Talaqi, Muroja'ah, Sima'I methods and Kitabah in memorizing Al-Qur'an at the boarding school Tahaffudhul Qur'an. The design of this research includes this type of research is field research. The nature of this research is descriptive research, namely a form of research that is shown to describe existing phenomena. The results showed the implementation of the Talaqi, Muroja'ah, Sima'I, and Kitabah methods in Islamic boarding schools Tahaffudhul Qur'an Miftahul Jannah, namely using more than one learning method. In memorizing Al-Quran, of course, it must always be accompanied by a sincere intention to ask permission from parents, have a big and strong determination.